Pengaruh Penyuluhan dengan Metode Whole Group-Discussion Terhadap Sikap dalam Pencegahan Kehamilan Remaja - Efvina Goemawati; Fitriani Mediastuti; Reni Tri Lestari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
ABSTRACT Background: Reproductive health is still a problem of public health that have large scales in Indonesia. Phenomenon that occurs in public during this indicates that sexual behavior youth and sex pre marriage in adolescents continually increase from year to year. One of prevention that can be for the provision is education through extension activities. Extension that used is by using the whole group discussion method that will be used to know attitude in the prevention teen pregnancy. This research have aims to know attitude in the prevention teen pregnancy with counseling uses the whole group discussion in junior high school 3 Kasihan. Method: This research using a kind of Quasi Experiment with one group pre test and post test design. The Population were 119 students in IX class. The sample collection with simple random sampling and there were 55 samples. The method of analysis data by using paired t test. Result: Based on the results of pre test and post test its mean value of pre test 61,75, while value post test 64,74. T count of -5,877 and the significance is 0,000 (p< 0.05). The results of the difference attitude before and after given intervention that its mean value post test is higher than its mean value pre test. The conclution of reserch is a change in attitude students IX class in teen pregnancy prevention in state given intervention in the form of counseling with the methods whole group discussion. Keywords: Teenagers, counseling, a method of whole group discussion, teen pregnancy.